The validity and reliability of the Basketball Jump Shooting Accuracy Test. Issue 14 (18th July 2019) - Boddington, Brenton J.; Cripps, Ashley J.; Scanlan, Aaron T.; Spiteri, Tania
ABSTRACT: The aim of this study was to examine the content validity, construct validity and reliability of the newly developed Basketball Jump Shooting Accuracy Test (BJSAT). Basketball athletes from different playing levels (State Basketball League [SBL], n = 30, age: 22.7 ± 6.1 yr; SBL Division I, n = 11, age: 20.6 ± 2.1 yr) completed four separate trials of the BJSAT with each trial consisting of shot attempts from two- and three-point distances at pre-determined court locations. Each shot attempt was scored utilising a criteria where higher scores were given when greater accuracy was exhibited. The BJSAT detected a significant, large difference in accuracy between two- and three-point shots ( d  = 0.99, p < 0.01). Relative reliability across the repeated trials was rated as moderate for all athletes (intraclass correlation coefficient [ICC] = 0.71, p < 0.01) and good for the SBL athletes (ICC = 0.78, p < 0.01). Absolute reliability for all athletes was above the acceptable benchmark (coefficient of variation = 16.2%); however superior to skill tests available in the literature. In conclusion, the BJSAT is sensitive to two- and three-point shooting accuracy and can reliably assess jump shooting accuracy in basketball athletes.